DISPOSITIONAL EVENTS THAT PROBABILIZE THE PRACTICE OF RISK BEHAVIORS RELATED TO HIV/AIDS - Piña López, Julio Alfonso (Anales de Psicología / Annals of Psychology, 2004)
The results of a study are presented that had as main objective to evaluate the capacity of prediction of dispositional events (knowledge, beliefs, social circumstances and reasons) on the practice of four risk behaviors to the infection for HIV in a sample of university students. Of such events, the reasons only evidenced their prediction power on all the risk behaviors. The results are analyzed in function of the importance that they have to the incorporation of variables of motivational type in the design and setting in march of programs of prevention of the AIDS directed to the population’s sector.